The origin of the Arabs: a critical evaluation of the sources - Yaacob, Solehah@Nik Najah Fadilah (The Islamic Cultural Center and London Central Mosque, London, U.K, 2014)
The research will therefore concentrate on the origins of the Arabs and their language at that time. Jawad Ali, the author of the Abridged History of the Arabs before Islam (Mufassal ta’rikh al’arab qabl alislam) suggests that the Arabs can be divided into three major groups; namely the ‘lost Arabs’ (al-‘arab al-bÉ‘idah), second the ’true Arabs’ (al-‘arab al-Ñaribah), and third the Arabized Arabs (al-‘arab al-mustaÑrabah). Evidence for this division is recorded in Ibn Ishaq’s and Ibn Hisham’s Biography of the Prophet (alsirah alnabawiyyah) and Tabari’s History of the Communities and Kingdoms (Ta’rikh alumam walmuluk). However, other scholars such as ‘Abd alSalam al-Jumahi (a critic of early poetry) disagreed with Ibn Ishaq that poems by ÑAd and Thamud proved the existence of the Arabs as a people before the time of Prophet Ibrahim (a.s). The biographer Ibn NadÊm considered the verses cited by Ibn Ishaq as fraudulent and not genuine. It is a well-established fact that the corpus of ancient Arabic poetry had suffered a lot at the hands of forgers, plagiarists, misguided philologists, and dishonest narrators. For instance, a number of poems were falsely ascribed to HassÉn bin Thabit, Prophet`s poet. Thus, this study aims at examining and assessing the validity of the Muslim sources on the issue pertaining to the origins of Arabs as a people. Keywords: Controversy, Sources, Plagiarism, Poems, Critics